A REVIEW ON CONTRIBUTION OF ACHARYA SUSHRUTA IN EMERGENCY SURGICAL CONDITIONS - Richa Sharma; P. Hemantha Kumar (International Journal of Ayurveda and Pharma Research, 2020)
Acharya Sushruta was the ancient Indian surgeon and also called as Father of Surgery. In ancient era when surgery was in its early childhood stage or not even heard of in other parts of the world, Acharya Sushruta performed surgery in various emergency conditions like Chhidrodara (intestinal perforation), Baddhgudodara (intestinal obstruction), Ashmari (urolithiasis), Sadyo Vrana (traumatic wound), etc. In his text Sushruta Samhita, he described all such types of diseases and their emergency surgery. His basic principles of plastic surgeries and concept of anesthesia are the privilege to emergency surgery. Ashtavidha Shastra Karma (8 types of surgical procedures), trauma bandage, emergency trauma suturing, management of Raktasrava (hemorrhage), replacement of blood volume, etc., are the basic principles of emergency surgery and given by Acharya Sushruta first. There are various advanced types of surgical procedures available in modern science for emergency conditions, but many of these surgical procedures are still following the basic principles as given by Acharya Sushruta and even after their development, in certain conditions they are still deprived of. So this paper focuses on review on the contribution of Acharya Sushruta in emergency surgical conditions.